The Iraqi national anthem An analytical study (Journal of the College of Basic Education, 2023)
The Chinese philosopher Confucius (born in 551 BC) say (If you want to know people civilization listen to their music) takes the music its role and its position in the welcome and farewell of the official heads, kings, princes and ministers guests, through the national anthem of the country, so the first thing seen by the presidents or kings, or ministers the level of music that the country through its music by Army band play the national anthem.The Research consists of six axes, we dealt with in the 1st axis from methodological framework for research and previous studies, while in the 2nd axis we approached the entrance of the historic of national anthems in the world, the languages of national anthems, the use of the national anthem, and in the 3ed axis of the research we dealt with the royal anthem of Iraq (1924-1958), the national anthem of Iraq (1958 - 1963), the national anthem of Iraq (1963 - 1981), the national anthem of Iraq (1981 -2003), the national anthem of Iraq since 2003 until the completion of the research, In the 4th axis we dealt with action research and the research community, the standard analysis of music, validity and reliability of the research tools. In the 5th axis has been full music analysis of the national anthem of Iraq (Mawtini), and finally concluded 6th Axis findings, conclusions and recommendations as well as sources and references of the research.